2010
DOI: 10.1167/10.13.7
|View full text |Cite
|
Sign up to set email alerts
|

The default allocation of attention is broadly ahead of smooth pursuit

Abstract: When moving through our environment, it is vital to preferentially process positions on our future path in order to react quickly to critical situations. During smooth pursuit, attention may be directed ahead with either a focused locus or a broad bias. We examined the 2D spatial extent of attention during a smooth pursuit task using both saccade (SRT) and manual (MRT) reaction times as measures of attentional allocation. Targets were flashed at various locations around current eye position while subjects purs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 79 publications
4
58
3
Order By: Relevance
“…Whereas no study has explored predictive shifts of covert attention in early visual areas, recent single-cell recordings in monkeys (Niebergall et al 2011) and event-related potentials in humans (Drew et al 2009;Doran and Hoffman 2010;Störmer et al 2013) have shown that visual responses in striate and extrastriate cortical areas show enhanced responses to tracked compared with untracked objects. Finally, during smooth pursuit, visual performance is highest at the current position of the target (Lovejoy et al 2009) or even ahead of it (van Donkelaar and Drew 2002; Khan et al 2010), both of which require predictive shifts of attention to compensate for the neural delays of the visuomotor system. Together, these findings hint at a possible neural architecture underlying the attentional enhancement in visual performance along the predicted motion path: attention-related areas index the current and future locations of a tracked object and facilitate visual processing at these locations by altering visual signals in striate and extrastriate cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas no study has explored predictive shifts of covert attention in early visual areas, recent single-cell recordings in monkeys (Niebergall et al 2011) and event-related potentials in humans (Drew et al 2009;Doran and Hoffman 2010;Störmer et al 2013) have shown that visual responses in striate and extrastriate cortical areas show enhanced responses to tracked compared with untracked objects. Finally, during smooth pursuit, visual performance is highest at the current position of the target (Lovejoy et al 2009) or even ahead of it (van Donkelaar and Drew 2002; Khan et al 2010), both of which require predictive shifts of attention to compensate for the neural delays of the visuomotor system. Together, these findings hint at a possible neural architecture underlying the attentional enhancement in visual performance along the predicted motion path: attention-related areas index the current and future locations of a tracked object and facilitate visual processing at these locations by altering visual signals in striate and extrastriate cortex.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts to the eye movements after head movements to shift gaze by top-down attention or during a task-related gaze shift as viewing static images [11]. Second, the eyes track the object smoothly (pursuits eye movements) when viewers look at a moving object [12,13]. And the eyes can ignore the motion caused by self-motion [14].…”
Section: Introductionmentioning
confidence: 95%
“…Attention is or can readily be allocated ahead of a moving target during predictive visual tracking (Khan, Lefèvre, Heinen, & Blohm, 2010; Lovejoy, Fowler, & Krauzlis, 2009; van Donkelaar & Drew, 2002). Such attention allocation is usually covert in that the gaze is maintained on the target; that is, the urge to shift the gaze to the center of attention away from the target is suppressed.…”
Section: Discussionmentioning
confidence: 99%